TEACHER'S ATTEMPT IN IMPROVING STUDENTS' MAHAROH KALAM: STRATEGIES, PROGRAMS, AND ITS PROBLEMS - Dian Ahmad Jufrih; Zul Ikrom Zilsafil; Uril Bahruddin; Ahmad Syakirin Asmu'i (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Improving Maharoh Kalam is a must for Arabic learners at all levels. This paper describes the teacher's attempt in improving the Maharoh Kalam of elementary school students based on the Tahfidz Qur'an. The researchers adopt a descriptive qualitative approach with a case study method at Tahfidz Al-Qur'an Daarul Ukhuwwah Elementary School in Malang. The results of the research indicate that a) the learning strategy while playing totally attracts the students’ attention to the Arabic learning subject, b) the Arabic language learning program must be followed by teachers and students, and c) the obstacles found from the late submission of Mufrodat. The findings of the research indicate the positive impact that arises from the game-based Arabic language learning process comes from the students who are able to communicate the Arabic language with their teachers and friends. Schools, teachers, and students’ guardians can be more synergized so that students' speaking skills can be effective.